Mini-intronic plasmid vaccination elicits tolerant LAG3+ CD8+ T cells and inferior antitumor responses. (2nd October 2016) - Colluru, Viswa Teja; Zahm, Christopher D.; McNeel, Douglas G.
ABSTRACT: Increasing transgene expression has been a major focus of attempts to improve DNA vaccine-induced immunity in both preclinical studies and clinical trials. Novel mini-intronic plasmids (MIPs) have been shown to cause elevated and sustained transgene expression in vivo . We sought to test the antitumor activity of a MIP, compared to standard DNA plasmid immunization, using the tumor-specific antigen SSX2 in an HLA-A2-restricted tumor model. We found that MIP vaccination elicited a greater frequency of antigen-specific CD8 + T cells when compared to conventional plasmid, and protected animals from subsequent tumor challenge. However, therapeutic vaccination with the MIP resulted in an inferior antitumor effect, and CD8 + tumor-infiltrating lymphocytes from these mice expressed higher levels of surface LAG3. Antitumor efficacy of MIP vaccination could be recovered upon antibody blockade of LAG3. In non-tumor bearing mice, MIP immunization led to a loss of epitope dominance, attenuated CD8 + cytokine responses to the dominant p103 epitope, and increased LAG3 expression on p103-specific CD8 + T cells. Further, LAG3 expression on CD8 + T cells was associated with antigen dose and persistence in spite of DNA-induced innate immunity. These data suggest that for antitumor immunization, approaches leading to increased antigen expression following vaccination might optimally be combined with LAG3 inhibition in human trials. On the other hand, mini-intronic vector approaches may be a superior means to elicit LAG3-dependent tolerance in the treatment of autoimmune diseases.